Functional components in extracts of Beta vulgaris (Chukandar) parts for antioxidant effect and antiobesity potential with lipase inhibition. (June 2021) - Chaturvedi, Swati; Gupta, Promila
Abstract: The development of plant-derived dietary supplements and drugs to treat the obesity epidemic has increased. These supplements may target oxidative stress and pancreatic lipase (PL) catalyzed fat digestion to manage lipid metabolism. Therefore, inhibition of PL and neutralization of reactive oxidants may be potential solutions to obesity management. In the present study, various extracts of 4 parts of Beta vulgaris (BV) were quantified for total phenolics, flavonoids, and saponins contents. Of these, methanolic extracts of leaves (BVLM), acetone extracts of petiole (BVPA), and leaves and petiole saponin extracts (BVLS and BVPS) were further evaluated using the FRAP assay and free radicals scavenging (DPPH and ABTS + radicals) potentials. BVLM (DPPH - EC50 100 ± 10 μg/ml) and BVLS (ABTS + - EC50 6.7 ± 2.0 μg/ml) showed the strongest scavenging activities whereas, BVPS had the highest FRAP value (107 ± 4 μg Trolox equivalents/mg dry extract). Their porcine PL inhibition potential was evaluated. BVLS showed the most effective inhibition (68 ± 2% at maximum concentration and mixed mode) followed by BVLM. GC-MS characterization of bioassay-guided potential extracts (BVLS and BVLM) showed the presence of many volatile compounds, their derivatives, and other drug candidates. The data was visualized using principal component analysis that explained the data variance by 70.1 and 79.3% for crude solvent extracts and saponin extracts, respectively. 2-Benzylpiperidine and phytol were docked with PL to complement the inhibition results. Therefore, BVLS and BVLM extracts may be studied further as potentially beneficial sources of bioactives to regulate fat assimilation. Highlights: B. vulgaris leaf methanolic and crude saponin extracts had the best antioxidant activity. Saponin extract inhibited pancreatic lipase (PL) better than methanolic extract. Various known antioxidants and antiobesity components were detected using GC-MS. 2-Benzylpiperidine and phytol showed good binding affinity with PL, in silico. The results obtained in the study were statistically correlated.